The marketisation of English higher education : a policy analysis of a risk-based system - McCaig, Colin, Dr. (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book traces the development of a fully marketised higher education system in England over a 30-year period and identifies five distinct stages of market reforms culminating in the Higher Education and Research Act (HMSO, 2017). The Act shifted the risks of institutional failure (and the prospect of market exit) onto applicants, presenting them with ever more applicant choice information and encouraging them to use their consumer behaviour to oblige weaker providers lower tuition fees or lose market share to new competitors. The new regulatory regime represents a marked departure from previous attempts to introduce market dynamism into the sector and places the English HE system at the forefront of a global trend of system marketisation. The book employs a critical policy discourse analysis and addresses several key aspects of the current higher education policy landscape. It considers the extent to which there been a continuity of policy from the encouragement of efficiencies and accountability in the 1980s to the emphasis on competition and risk in 2017; whether the marketisation process is designedly cumulative or has developed in response to factors beyond the control of policymakers; and what the English case can tell us about the nature of neoliberalism and the future trajectories of other national systems in the process of marketising and differentiating their institutions.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Education, Higher -- Great Britain; Education -- Higher; Higher & further education, tertiary education